Pediatric Atypical Progressive Acute Kidney Injury In Indonesia - Mahrunnisa, Fitria; Ripha, Roshida Fitri; Awaliyah, Vina Izzatul (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2023)
Background: In the last few months of the 2022, there has been an increase in pediatric acute kidney injury cases with high mortality in Indonesia. Atypical progressive acute kidney injury (AKI) described as duration of the development of the disease into end stage stadium occured rapidly and abruptly result in high mortality indicates more than 50% despite received dialysis treatment. The cases were dominated by previously healthy toddlers age less than five years old without comorbidities. This review presents necessary informations related to etiology, diagnosis and management of atypical progressive AKI. This review also discuss about the etiology although the spesific causes are still widely studied as well as reports of new events on the causes of AKI. Methods: Systematic review of studies about atypical progressive acute kidney injury, the situation that is occurring at the moment in Indonesia.Results: There are spesific operational definition for diagnosing atypical progressive AKI in children including initial symptoms cover for infection symptoms of respiratory tract and gastrointestinal system and none history of previously kidney injury which also found both hyperinflamation or hypercoagulation signs. Most children were previously health children. Spesific cause are still unknown but some children were found positive for viral and bacterial infection, SARS COV-2 antybody and also ethylene glycol intoxication as reported cases in Gambia by WHO.Conclusion: When compared to the pediatric community AKI in general, certain variations were discovered in the atypical pogressive type of AKI, known patient features, initial symptoms, and etiology.